A solution for fault tolerance in replicated database systems. (5th June 2006) - Chen, Changgui; Zhou, Wanlei
A distributed database system is subject to site failure and link failure. This paper presents a reactive system approach to achieving fault tolerance in such a system. The reactive system concepts are an attractive paradigm for system design, development and maintenance because it separates policies from mechanisms. In the paper we give a solution using different reactive modules to implement the fault tolerant policies and the failure detection mechanisms. The solution shows that they can be separated without impact on each other; thus the system can adapt to constant changes in environments and user requirements.